Upaya Meningkatkan Keterampilan Berpikir Kritis Siswa Melalui Penerapan Model Pembelajaran Cooperative Script di Sekolah Dasar - Nur Syamsyiah (STKIP Andi Matappa Pangkep, 2022)
Critical thinking skill is one of 21st century vital skills that should be mastered by students to face global challenges. Unfortunately, critical thinking skills possessed by many students are still not well developed. This study aims to determine the implementation of the Cooperative Script learning model to improve critical thinking skills of grade VI students at SDN Panglegur 2 Pamekasan. The research used in this study was Classroom Action Research (CAR) which consists of 2 cycles. Each cycle consists of planning, implementing, observing, and reflecting activities. The results of this study showed that there was an increase in the average score of students' critical thinking skills. The average score on the initial test was 60.65 or it was included in the category of sufficient critical thinking; the average score in the 1st cycle was 67.91 or it was still in the sufficient category; and in the 2nd cycle rose to 74.52 or in the good category. At the end of the 2nd cycle, as many as 17.39% of students reached the category of very good critical thinking skills. Thus, it can be concluded that the implementation of the Cooperative Script learning model can improve students' critical thinking skills.